Aktivitas Analgetik dan Antiinflamasi Fraksi Daun Ashitaba (Angelica keiskei (Miq.) Koidz.) Pada Tikus Jantan Galur Wistar dan Keamanannya Terhadap Lambung - EKA NDHARI ROCHMA (Fakultas Farmasi Universitas Setia Budi, 2022)
Ashitaba (Angelica keiskei (Miq.) Koidz.) is a plant that has analgesic and anti-inflammatory activity. The content of compounds which are thought to be efficacious are flavonoids, saponins, alkaloids, and tannins. The purpose of this study was to determine the extracts and fractions having analgesic activity with the hot plate and tail flick method, anti-inflammatory activity with the randall-selitto method and the formation of udema, safety of the stomach and to find out which fraction provided the strongest and safest activity against the rat's stomach. Ethanol extract of Ashitaba leaf was fractionated with n-hexane, ethyl acetate, and water. The analgesic test was carried out by the hot plate and tail flick method, the anti-inflammatory test was carried out by the randall-selitto method and the formation of edema was then examined by the rat's gastric safety using macroscopic and microscopic.The dosage of Ashitaba leaf extract and fractions were extract 300 mg/kgBB, n-hexane fraction 120.7 mg/kgBB, ethyl acetate fraction 20.6 mg/kgBB, water fraction 158.65 mg/kgBB, negative control of Na CMC 1%, and negative control of Na CMC 1% mefenamic acid 500 mg/kgBB. The results showed ethanol extract, n-hexane fraction, ethyl acetate fraction, and water fraction Ashitaba leaf had analgesic and anti-inflammatory activity. Extract 300 mg / kg body weight and n-hexane fraction 120.7 mg / kg body weight showed analgesic and anti-inflammatory activity equivalent to mefenamic acid and showed safety in the stomach equivalent to negative control.